Pharmacognostic and Physico-chemical standardization of Macrotyloma uniflorum (Lam.) verdc. edible seed - Papiya, Bigoniya; Sourabh, Vyas; Alok, Shukla; Chandra Shekhar, Singh (Pharmacognosy Communications)
Introduction: Macrotyloma uniflorum (Lam.) Verdc. (Family Fabaceae) commonly known as horse gram is largely cultivated in Australia, Burma, India and Sri Lanka. In the present study an attempt has been made to standardize this ethnopharmacologically useful seed on the basis of pharmacognostical, physico-chemical and phytochemical characteristics. Methods: The external morphology of seed was observed by using simple microscope. The percentage of foreign matter, loss on drying, crude fiber, swelling and foaming index of dried seed powder were determined. Total ash, water soluble ash, acid insoluble ash, sulphated ash and fluorescence property were also determined. Extraction, qualitative and quantitative analysis of seed samples was measured for total phenols and tannins and total flavonoids, along with TLC and HPTLC. Results: The seeds were odorless, slightly acrid and nonaromatic. The loss on drying was 1.45%, the total ash was 7.95% and the water soluble ash was 2.90% whereas acid insoluble and sulfated ash showed low content (3.10 and 1.81% respectively). Acetone (18.42%) and methanol (15.58%) soluble extracts showed the presence of alkaloid, glycoside, steroid, triterpenoid, carbohydrate, tannin, phenolics, saponin, flavonoid, amino acid and mucilage (except starch) phytoconstituents. The methanol extract was rich in flavonoid (8.59 mg/gm) whilst the acetone extract showed a high content of total polyphenols and tannins (8.91 and 5.23 mg/gm respectively). TLC showed the presence of chlorogenic acid and ferulic acid, whereas HPTLC confirmed the presence of quercetin and chlorogenic acid. Conclusion: The present study established pharmacognostic, physico-chemical, phytochemical, microscopic and fluorescence characterizations of M. uniflorum seed along with identification of bioactive flavonoid compounds.
Keywords: Flavonoid; HPTLC; M. uniflorum; Seed microscopy; TLC; Quantitative estimation